Plant-based proteins for infant formula: findings and recommendations from the ILSI Europe workshop - Hettinga, Kasper A.; van den Akker, Chris H. P.; Billecke, Nils; Cardinaals, Renée; Chang, Ching-Yu; Dupont, Didier; Furber, Matthew; Grimshaw, Kate; Hallam, Paula; de Jong, Peter; Keppler, Julia K.; van Loo-Bouwman, Carolien A.; et al. (Frontiers in Nutrition, 2025)
This Review Article summarizes outcomes from the ILSI Europe expert workshop on plant-based proteins in infant formula, held in November 2024. Experts from academia, clinical nutrition, and food science evaluated the current use and future potential of plant-based protein sources in infant formula, considering nutritional adequacy, allergenicity, sustainability, processing technologies, and regulatory constraints. While soy and hydrolyzed rice proteins are already approved and in use, emerging sources such as pea, lentil, and faba beans show promise but require further validation of their amino acid profiles, digestibility, safety, and suitability for infants. Key research priorities identified include the development of improved protein extraction methods, in vitro digestion and allergy modeling, and targeted clinical studies. This review synthesizes current evidence and expert perspectives to support the development of sustainable, nutritionally adequate plant-based infant formulas.